Volcanic Tremor Tracks Changes in Multi‐Vent Activity at Mt. Etna, Italy: Evidence From Analyses of Seismic Array Data. Issue 22 (16th November 2022) - Zuccarello, L.; De Angelis, S.; Minio, V.; Saccorotti, G.; Bean, C. J.; Paratore, M.; Ibanez, J. M.
Abstract: The mild degassing and effusion that characterizes open‐vent volcanoes can be interrupted by episodes of sustained explosive activity known as paroxysms. Here, we present observations from a seismic array deployment during the 2021 eruption of Mt. Etna, Italy. During the observation period, degassing dominated surface activity at the central and northeast summit craters; lava flows, Strombolian explosions, and fire fountaining, accompanied by ash plumes, characterized eruption in the southeast sector of Mt. Etna. Seismic array locations showed changes associated with shifts in the style and location of activity across multiple craters at Mt. Etna. We observed changes in array locations between the north‐northeast and southeast directions that consistently anticipated the onset of paroxysmal activity in the southeast sector. Our results demonstrate the potential of seismic arrays to resolve vent‐specific activity and shed light on precursory patterns leading up to paroxysmal activity. Plain Language Summary: In this study we present analyses of seismic data collected at Mt. Etna, Italy, during a period of paroxysmal eruptive activity in the summer of 2021. Throughout the period under investigation, activity at the volcano was characterized by shifts in both style and location across the multiple summit craters. Analyses of seismic data recorded by a cluster of tightly spaced seismometers, or seismic array, allowed to track the location of seismic tremor throughout the study period. We show, with unprecedented resolution, that migration of the tremor source systematically anticipated the onset of the most intense phases of eruption. Our results are consistent with previously proposed models of a branched conduit system within the shallow plumbing at Mt. Etna; different branches of the conduit system feed activity from different vents within the multiple summit craters, each with a distinctive style of eruption. The results of our study demonstrate that seismic arrays can shed light on precursory patterns leading up to paroxysmal activity at Mt. Etna, and other similar volcanoes worldwide. We surmise that seismic arrays are a powerful monitoring tool with clear potential to improve volcano early warning practices and protocols. Key Points: Seismic arrays track degassing and explosive activity at multi‐vent volcanoes Systematic shifts in seismic tremor locations anticipate the onset of paroxysmal activity at Mt. Etna Shifts in tremor locations and style of surface activity at Mt. Etna are consistent with previous models of a branched conduit system